First Report of Dramatic Tumor Responses with Ramucirumab and Paclitaxel After Progression on Pembrolizumab in Two Cases of Metastatic Gastroesophageal Adenocarcinoma. (19th April 2018) - Chakrabarti, Sakti; Dong, Haidong; Paripati, Harshita R.; Ross, Helen J.; Yoon, Harry H.
Abstract : Checkpoint inhibitors targeted at programmed cell death‐1 receptor (PD‐1) and its ligand (PD‐L1) can result in significant benefit to a small proportion of patients with cancer, including those with tumors of the stomach and gastroesophageal junction. These drugs are now approved for several solid tumors, including the recent accelerated approval of pembrolizumab for gastroesophageal adenocarcinomas in the third‐line setting and beyond based on the KEYNOTE‐059 phase II trial. Data are lacking on the efficacy of chemotherapy after progression on PD‐1 blockade in metastatic gastroesophageal adenocarcinoma. This report describes the exceptional response of two patients who received ramucirumab plus paclitaxel after progressive disease on pembrolizumab. This early clinical observation suggests that the sequence of administration of PD‐1 blockade and chemotherapy may be important in this disease. Abstract : This brief communication reports the efficacy outcomes of two patients who experienced dramatic tumor response on ramucirumab plus paclitaxel after progressive disease on pembrolizumab.